1999
DOI: 10.1016/s0960-9822(99)80023-2
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila TNF-receptor-associated factor (TRAF) binds the Ste20 kinase Misshapen and activates Jun kinase

Abstract: Two families of protein kinases that are closely related to Ste20 in their kinase domain have been identified - the p21-activated protein kinase (Pak) and SPS1 families [1-3]. In contrast to Pak family members, SPS1 family members do not bind and are not activated by GTP-bound p21Rac and Cdc42. We recently placed a member of the SPS1 family, called Misshapen (Msn), genetically upstream of the c-Jun amino-terminal (JNK) mitogen-activated protein (MAP) kinase module in Drosophila [4]. The failure to activate JNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(103 citation statements)
references
References 19 publications
2
101
0
Order By: Relevance
“…Several mechanisms have been identified that activate JNK and induce apoptosis in wing imaginal discs. For example, mutations in the caspase inhibitor DTraf1 (Drosophila tumor necrosis factor receptor-associated factor 1), as well as inhibition of DTraf1 by overexpression of Hid (head involution defective), Rpr (reaper), or Grim, induces JNK-mediated apoptosis Ryoo 2004), possibly through Msn (misshapen) or Ask1 (apoptosis signal-regulating kinase 1) (Liu 1999;. Other factors involved in inducing apoptosis and activating JNK are Eiger (Drosophila tumor-necrosis factor superfamily ligand) , its receptor Wengen (Kauppila 2003), Src42A (Tateno 2000), the serine C-palmitoyltransferase Lace (Adachi-Yamada et al 1999b), Blistery (Drosophila Tensin) (Lee et al 2003), and Decapentaplegic and Wingless (AdachiYamada et al 1999a).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been identified that activate JNK and induce apoptosis in wing imaginal discs. For example, mutations in the caspase inhibitor DTraf1 (Drosophila tumor necrosis factor receptor-associated factor 1), as well as inhibition of DTraf1 by overexpression of Hid (head involution defective), Rpr (reaper), or Grim, induces JNK-mediated apoptosis Ryoo 2004), possibly through Msn (misshapen) or Ask1 (apoptosis signal-regulating kinase 1) (Liu 1999;. Other factors involved in inducing apoptosis and activating JNK are Eiger (Drosophila tumor-necrosis factor superfamily ligand) , its receptor Wengen (Kauppila 2003), Src42A (Tateno 2000), the serine C-palmitoyltransferase Lace (Adachi-Yamada et al 1999b), Blistery (Drosophila Tensin) (Lee et al 2003), and Decapentaplegic and Wingless (AdachiYamada et al 1999a).…”
Section: Discussionmentioning
confidence: 99%
“…The upstream regulators of Bsk include a series of kinases that form a signaling cascade (Stronach and Perrimon, 2002;Takatsu et al, 2000;Tateno et al, 2000;Xue et al, 2007). MSN, a MAPK kinase kinase kinase (MAPKKKK) receives signals from cell surface receptors and initiates this signaling cascade (Liu et al, 1999;Xue et al, 2007). While the main signaling pathway transmits from MSN to JNK hierarchically, other factors connected to this main pathway also function in fine-tuning of the signaling, especially in activating or repressing the JNK activity (Chen et al, 2002;Neisch et al, 2010;Shanley et al, 2001;Yang et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The Drosophila TNF/TNFR homologs are EIGER/WENGEN [9,10]. Three Drosophila members of the TRAF family have been identified [11,12]. The Drosophila homologs of the DED (Death Domain)-containing protein FADD and caspase-8 are dFADD and DREDD, respectively [13,14].…”
Section: Introductionmentioning
confidence: 99%